Chapter Culture and critique - Belia, Vasiliki (Amsterdam University Press, 2023)
In her work on cultural critique, Rosemarie Buikema conceptualizes culture as a terrain for the elaboration and contestation of collective memory, a form that mediates social formations, and a practice that critically supplements the political. Taking the polysemic relationship between culture and critique as our starting point, we bring Buikema's reflections to bear on our own work on post-Yugoslav visual art, feminist graphic narratives, and digital media. We pay special attention to the question of "medium specificity", which is central to Buikema's conceptual intervention. Our goal is to illustrate the expansive reach of this intervention across multiple fields of inquiry.